2015
DOI: 10.1128/mcb.01457-14
|View full text |Cite
|
Sign up to set email alerts
|

Elongation Factor 2 Kinase Is Regulated by Proline Hydroxylation and Protects Cells during Hypoxia

Abstract: Protein synthesis, especially translation elongation, requires large amounts of energy, which is often generated by oxidative metabolism. Elongation is controlled by phosphorylation of eukaryotic elongation factor 2 (eEF2), which inhibits its activity and is catalyzed by eEF2 kinase (eEF2K), a calcium/calmodulin-dependent ␣-kinase. Hypoxia causes the activation of eEF2K and induces eEF2 phosphorylation independently of previously known inputs into eEF2K. Here, we show that eEF2K is subject to hydroxylation on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 65 publications
(72 citation statements)
references
References 51 publications
2
70
0
Order By: Relevance
“…Given that N-lobe based interactions are weaker with respect to those involving the C-lobe, and themselves do not appear to be critical, hydroxylation of P98 should have a relatively small effect on CaM binding, in agreement with the data of Moore et. al (Moore et al, 2015). In the same study it was also shown that mutation of W99 ( W99A , W99L ) does not lead to a significant reduction in CaM binding, as expected from our structure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that N-lobe based interactions are weaker with respect to those involving the C-lobe, and themselves do not appear to be critical, hydroxylation of P98 should have a relatively small effect on CaM binding, in agreement with the data of Moore et. al (Moore et al, 2015). In the same study it was also shown that mutation of W99 ( W99A , W99L ) does not lead to a significant reduction in CaM binding, as expected from our structure.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the W85S mutant is severely compromised in its ability to phosphorylate eEF-2 in cells. Recent studies have shown that hydroxylation on P98 (also fully conserved, Figure S8) by hydroxylases, that are inactivated during hypoxic conditions, lead to activation of eEF-2K and impaired protein translation (Moore et al, 2015). We have shown that P98 contributes to the engagement of the N-lobe and based on our structure it is conceivable that the introduction of a polar group on P98 would reduce its hydrophobic interactions with the N-lobe of CaM.…”
Section: Discussionmentioning
confidence: 99%
“…During hypoxia, eEF2K is activated by a mechanism that involves proline hydroxylases, which require oxygen as a co-substrate and are involved in other effects of hypoxia, such as the regulation of the transcription factor hypoxia-inducible factor 1α (HIF1α). However, the regulation of eEF2K by oxygen appears not to involve HIF1α, but rather, the direct hydroxylation of eEF2K at a highly conserved proline (Pro98; Figure 1, 2) adjacent to the CaM-binding site [22] ; this residue is in a strongly conserved motif in the 'linker' between the CaMbinding motif and the catalytic domain of eEF2K. This modification limits the ability of CaM to activate eEF2K, keeping its activity low in oxygenated conditions.…”
Section: Overview Of the Structure And Control Of Eef2kmentioning
confidence: 99%
“…eEF2K is a calcium/calmodulin-dependent (CaM) α kinase. Hypoxia or prolyl hydroxylase inhibition was reported to activate eEF2K kinase activity, thereby contributing to increased eEF2 phosphorylation [106]. As a result, cells demonstrate decreased translation elongation and protein synthesis under hypoxia, which protects them from excessive usage of ATP.…”
Section: Novel Hydroxylation Targets and Their Cellular Functionsmentioning
confidence: 99%